THU0315 Patient-perceived involvement in disease management drives patient-physician alignment in satisfaction with disease control in psoriatic arthritis. (12th June 2018) - Gossec, L.; Orbai, A.-M.; Lobosco, S.; Moon, R.; Massey, O.; Piercy, J.; Cappelleri, J.C.; Fallon, L.; Young, P.; Romero, A.B.; Hsu, M.-A.
Abstract : Background: Previous analyses have indicated misalignment between Psoriatic Arthritis (PsA) patients and their physicians can be frequent, and can result in worse disease severity and health-related quality of life 1, 2. Factors associated with this misalignment have not been determined. Objectives: To assess patient-physician misalignment regarding satisfaction with PsA disease control and identify factors associated with this misalignment. Methods: Data were drawn from the Adelphi PsA Disease Specific Programme, a real-world survey conducted in 2015 across the US, France, Germany, Italy, Spain, UK. Patients had physician-confirmed PsA and had to have been receiving their current synthetic-DMARD (biologic naïve) or biologic therapy for at least 6 months. Physicians and patients independently provided information on satisfaction with disease control on a 5-point scale (very satisfied/satisfied/neither/dissatisfied/very dissatisfied). Physician and patient reports of satisfaction were compared to assess levels of misalignment. Physicians also provided information on demographics and disease history/severity. Patients provided information on involvement in treatment decisions, EuroQol-5D Visual Analogue Scale (EQ-5D), Work Productivity and Activity Impairment (WPAI) and Health Assessment Questionnaire Disability Index (HAQ-DI). Factors associated with misalignment were analysed by a multivariate logistic regression modelled using predictors identified as significant in univariate logistic regression. Data entered in the analyses included demographics, time diagnosed, treatment history, disease severity, flaring, pain, patient-reported involvement in treatment decisions, EQ-5D, WPAI, HAQ-DI. Results: 519 physicians (331 rheums, 188 derms) provided data for 2467 PsA patients, 656 meeting all inclusion criteria. Mean age was 49.9 (SD 12.1) years, mean disease duration 6.7 (6.2) years, 53.8% patients were male and 66.1% employed. Satisfaction with disease control was generally high amongst both patients (78.3%) and physicians (91.9%) with alignment in 79.4% of cases. In 16.8% of cases there was misalignment where patients were dissatisfied but physicians satisfied. Multivariate logistic regression showed that worse HAQ-DI (OR [95% CI]: 0.54 [0.38–0.77], p=0.001), worse EQ-VAS (OR 1.03 [1.02–1.04], p<0.001), lack of involvement in treatment decisions (OR 1.26 [1.07–1.50], p=0.007) and physician-reported severe disease as opposed to mild (OR 0.20 [0.05–0.78], p=0.020) were all independently associated with misalignment. Conclusions: Satisfaction with disease control was generally high for both patients and physicians; however, misalignment was not rare. Patients had higher levels of symptoms/increased impact on activities where there was misalignment. An independent factor associated with misalignment was patient-perceived involvement in condition management. Improving patient-physician engagement in overall disease management may lead to greater patient satisfaction and patient-physician alignment. References: [1] Desthieux C, et al. Arthritis Care Res (Hoboken)2017Oct;69(10):1606–1611. [2] Furst DE, et al. Clin Rheumatol2017Sep;36(9):2045–2054. Disclosure of Interest: L. Gossec Grant/research support from: UCB, Lilly, Pfizer, BMS, Consultant for: AbbVie, BMS, Celgene, Janssen, Novartis, Pfizer, Roche UCB, A.-M. Orbai Grant/research support from: AbbVie, Celgene, Eli Lilly, Horizon, Janssen, Novartis, Pfizer, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer, UCB, S. Lobosco Employee of: Adelphi Real World, R. Moon Employee of: Adelphi Real World, O. Massey Employee of: Adelphi Real World, J. Piercy Employee of: Adelphi Real World, J. Cappelleri Shareholder of: Pfizer, Employee of: Pfizer, L. Fallon Shareholder of: Pfizer, Employee of: Pfizer, P. Young Employee of: Pfizer, A. Romero Employee of: Pfizer, M.-A. Hsu Shareholder of: Pfizer, Employee of: Pfizer